Experimental Exploration of Bearing Capacity of Clay with Multiple Inflatable Anchors. (14th December 2020) - Chen, Qiu-nan; Yang, Meng; Huang, Xiao-cheng
Abstract : Inflatable anchors have been applied to reinforce foundations because soft soil deposits have a low bearing capacity. However, previous research on the mechanical behaviors of inflatable anchors has focused on a single anchor. Since anchors are always used in a group, the uplift behavior of multiple inflatable anchors in soft soil should be investigated. A series of pull-out tests were conducted in this framework by changing the number, spacing, and layout of inflatable anchors. Additionally, the effect coefficient (ECO) of multiple inflatable anchors is discussed. It is found that the failure behavior of multiple inflatable anchors exhibits a three-stage curve: an initial linear stage, followed by nonlinear, and steady-state stages. In addition, the ultimate bearing capacity of multiple inflatable anchors is maximized if the ratio of the spacing of inflatable anchors to the equivalent expanding section diameter of an inflatable anchor is 6.84. It is recognized that the ECO of this new multiple inflatable anchor group is sometimes greater than 1, unlike that of conventional anchors, which have ECOs of less than 1. In addition, the layout of multiple inflatable anchors in the shape of a cinquefoil is recommended due to its high ECO.